Can social media networks like Facebook and Twitter influence the agenda-setting of traditional media? Two case studies from Egypt. - Oda, Salma Ibrahim (AUC Knowledge Fountain, 2018)
This research aims to examine if social media content that is widely shared or commented on can influence the agenda of traditional media on women issues namely the sexual harassment and undocumented marriages, to what extent and whether or not the same framing applies when the discussion moves from traditional media to social media. The topics chosen were related to sexual harassment and undocumented marriages which are two crucial, sensitive topics for Egyptian women. Three traditional media outlets were purposefully selected for this study channels. Interviews with the producers of the primetime TV showswere also conducted to assess how and to what extent they rely on social media to set their daily and weekly agenda of topics. These shows are “Sabaya Al Kheir” on Nahar TV, “Al Ashera Masaan” on Dream TV and “Hona Al Assema” on CBC Channel. An online analysis tool was used to measure the volume of online conversations and determine their sentiment. The results showed that social media trending topics such as sexual harassment and undocumented marriages do make it to traditional media especially if they are related to bigger societal issues like undocumented marriage and sexual harassment. Viral content also are more likely to reach traditional media, which follow the framing of online sentiment.